(untitled) (Acta Scientiarum. Education, 2015)
This article presents part of a broader research developed between July 2010 and October 2013 and proposes an analysis of the professional development of four children’s education teachers participating in a training-research group. The resource used to give support to the reflections was the production of (auto) biographical narratives stimulated by mnemonic resources such as photos, films, objects, etc. The analysis reflects their formative journeys and professional development. The fragments analyzed showed the progress of the teachers, from getting to know the school as a space for learning and professional development, remembering moments of initial training, teaching initiation and, later, investing in their career by means of new courses, lato and strictu sensu. The narratives also show that the teachers are aware of their obligation and of the complexity involved in educating a child universally, and of their vulnerability, as well as of the need for constructing their specific professional life that integrates knowledge on childhood in the 21st century.